AIDA-Based Analysis of TikTok Live Marketing at Bin Dawood Boutique Purwokerto - Maharani, Revalyna Octavia; Pritama, Argiyan Dwi; Oktaviana, Luzi Dwi (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
This study aims to analyze the TikTok Live strategy implemented by Bin Dawood Butik Purwokerto using the AIDA model as an analytical framework. This research employed a descriptive qualitative design, through observations of 10 TikTok Live sessions, in-depth interviews with a marketing administrator and a live host, and documentation. Data were analyzed through reduction, presentation, and conclusion drawing based on the AIDA framework, with triangulation applied to ensure validity. Bin Dawood Boutique’s TikTok Live strategy effectively implements the AIDA model. The attention stage is built through persuasive greetings, engaging visuals, and broadcast scheduling that aligns with audience activity patterns. The interest stage is strengthened through the use of TikTok’s interactive features and the delivery of clear, responsive product information. The desire stage develops through host transparency, emphasizing product benefits, and strategic urgency. The action stage is driven by the use of clear CTAs and seasonal factors, such as the Eid al-Fitr period and payday, which encourage consumers to make transactions. Cumulative TikTok sales reached more than 26,900 products, confirming TikTok Live’s significant contribution to overall sales performance. This study provides an empirical overview of how a local fashion business operationalizes each stage of the AIDA model on TikTok Live. As a limitation, the study focuses on a single case and relies on qualitative data, which may constrain generalization.